PENGARUH GAYA HIDUP, LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS MEDAN AREA MEDAN - Sahir, Syafrida Hafni; Ramadhani, Atika; Tarigan, Eka Dewi Setia (Universitas Medan Area, 2016)
This research heads for (1) knowing the influences of the life style to the consumer buying decision (2) to know influence of the halal labeling to the consumer buying decision. (3) to know influences of the price to the consumer buying decision. The study was conducted to 80 respendents representing the buyer population wardah cosmetic in economy faculty collagers of Medan Area University Medan. Simultantly this research head for knowing the influences of life style, halal labeling, and price to the buyer decisionsKeywords : Life style, Halal Label, Price, Buying Decisions.